1997
DOI: 10.1001/archinte.1997.00440260101014
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Sliding Scale Insulin Use in Medical Inpatients With Diabetes Mellitus

Abstract: Suboptimal glycemic control is common in medical inpatients with diabetes mellitus. The risk of suboptimal control is associated with selected demographic and clinical characteristics, which can be ascertained at hospital admission. Although sliding scale insulin regimens are prescribed for the majority of inpatients with diabetes, they appear to provide no benefit; in fact, when used without a standing dose of intermediate-acting insulin, they are associated with an increased rate of hyperglycemic episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(170 citation statements)
references
References 39 publications
7
162
0
1
Order By: Relevance
“…SSI simply reacts to hyperglycemia instead of preventing the occurrence of hyperglycemia and could lead to a higher glucose level variability, which might be associated with an inferior outcome. 77,78 Therefore, SSI alone is not recommended as inpatient glucose control. [79][80][81] Basal-bolus insulin (BBI) is more reliable for inpatient glucose control.…”
Section: Treatment/management Of Ptdmmentioning
confidence: 99%
“…SSI simply reacts to hyperglycemia instead of preventing the occurrence of hyperglycemia and could lead to a higher glucose level variability, which might be associated with an inferior outcome. 77,78 Therefore, SSI alone is not recommended as inpatient glucose control. [79][80][81] Basal-bolus insulin (BBI) is more reliable for inpatient glucose control.…”
Section: Treatment/management Of Ptdmmentioning
confidence: 99%
“…10,11 The use of correction insulin-the so-called sliding scale-without concurrent use of basal insulin in the hospital results in ineffective control of hyperglycemia. 12,13 In noncritically ill medical and surgical inpatients, the most efficacious insulin program to treat glucose levels above recommended targets consists of a combination of long-acting basal insulin and short-acting insulin with meals when the patient is eating, supplemented by correction doses for high glucose values. [14][15][16] Clinical inertia is defined as the failure to intensify therapy when needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence supporting the effectiveness of SSI alone is lacking, and it is not recommended by the American Diabetes Association. 13 Queale et al 14 showed that SSI regimens when used alone were associated with suboptimal glycemic control and a 3-fold higher risk of hyperglycemic episodes. 1 Two retrospective studies have also demonstrated that SSI is less effective and widely variable in comparison with proactive preventative therapy.…”
Section: Discussionmentioning
confidence: 99%